IMPLEMENTATION OF SCHOOL-BASED MAINTENANCE AND OTHER OPERATING EXPENSES (MOOE) FUNDS AND CHALLENGES ENCOUNTERED AS PERCEIVED BY THE TEACHERS - Ureta, Allien A (President University, 2024)
This study sought to determine the degree of implementation of school-based MOOE funds and the challenges encountered as perceived by 320 teachers in local schools in the Philippines. Province of Capiz. The descriptive-correlational design was used in the study. The correlational design was used to determine the relationships between the degree of implementation of School-based MOOE funds in terms of disbursement and utilization and the challenges encountered as perceived by the teachers in terms of instructional and physical plant development. Statistical Package for Social Sciences (SPSS) was used for analysis of weighted mean. The Pearson-r was used to determine the significant relationships between two independent variables. The results shows a very high implementation in terms of disbursement and utilization There was no significant difference in the degree of implementation and when respondents are grouped according to profiles. There was no significant difference in the extent of challenges encountered and when respondents are grouped according to age, years in service and positions, but not in respondents’ sex. There was a significant relationship between the degree of implementation and the extent of challenges encountered as perceived by teachers. It implied that the degree of implementation was directly related with their extent of challenges encountered by the teachers. Qualitative data were taken from in-depth interview. The findings showed that during in-depth interview they were both significantly support to the quantitative result of the study.